Studi Komparatif Penggunaan Bahasa Indonesia dalam gaya bahasa Mahasiswa 1E Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Sherly emri Sherly emri maulida (Jurnal Lazuardi, 2026)
Indonesian plays a crucial role as the national language and academic language in higher education. For students, particularly those in the 1E program of Elementary School Teacher Education (PGMI) at UIN Sulthan Thaha Saifuddin Jambi, language holds significant value in everyday communication. Naturally, various barriers arise in using language. Despite the richness of language, there are barriers that can undermine interpersonal relationships due to language differences. These linguistic differences give rise to problems such as disintegration due to language differences and impaired communication. Many students retain a strong grasp of their regional languages, which carry over into the university environment. Students who tend to use regional languages typically use them to communicate with friends from the same region.